Strengthening the Merit System in Accelerating Bureaucratic Reform in Tangerang Regency - Syah, Ardy Firman; Marsono, ‎; Susilo, Slamet Rahmat Topo (KnE Social Sciences, 2025)
Bureaucratic reform is a key innovation aimed at enhancing efficiency, effectiveness, and accountability in government operations. A critical component of this reform is the merit system index, which serves as one of the key indicators in evaluating the success of general bureaucratic reform. This study aims to provide an in-depth analysis of the merit system assessment indicators in Tangerang Regency, Indonesia. Using a qualitative approach and the Root Cause Analysis (RCA) method, the research investigates the underlying causes of challenges in implementing the merit system. The findings reveal that a major issue in strengthening the merit system lies in the continued occurrence of promotions that are not based on competence and performance. To address this issue, a SWOT analysis was conducted to identify opportunities and formulate action plans for improvement. The study proposes integrating a Career Pattern System based on job competency development needs as part of the bureaucratic reform roadmap to reinforce the merit-based system.